SISTEM INFORMASI PELATIHAN PADA LEMBAGA ILMU PENGETAHUAN INDONESIA PUSAT PENGEMBANGAN TEKNOLOGI TEPAT GUNA BERBASIS WEB - Caca Arif Herdian (ZONAsi: Jurnal Sistem Informasi, 2023)
In 2017, services at the Indonesian Institute of Sciences Center for Appropriate Technology Development, especially in the training registration administration section, had not been computerized so that data was piling up and difficult when the data was needed. Based on the existing problems, the approach taken is to analyze and design a training information system and implement it into an application form that is used to support the delivery and management of training and education programs in helping plan, develop and provide training to employees, communities, and other stakeholders. other interests. So it is necessary to develop an information system that can be personalized, and adaptive so that it can be adjusted for prospective training participants. The development method uses the PHP programming language, the CodeIgniter Framework with the concept of Model, View, Controller (MVC), modeling using the Unified Modeling Language (UML), MySQL database, and the Unified Process (UP) work method. The modules contained in the training information system include the Participant module, the Institution module, the Resource Person module, the Service User module, and the External Services module.